2010
DOI: 10.1039/b913284h
|View full text |Cite
|
Sign up to set email alerts
|

Enormous enhancement in photocurrent generation using electrochemically fabricated goldnanostructures

Abstract: A self-assembled monolayer of porphyrins fabricated on the surface of an electrochemically deposited gold nanostructure exhibits enormous enhancement of photocurrent due to porphyrin excitation, especially in the near-infrared region, where localized surface plasmon resonance was responsible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
63
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 14 publications
3
63
0
Order By: Relevance
“…However, most important issue is to improve the efficiency of photoelectric conversion. One of the methods for upgrading these devices is the use of localized surface plasmon resonance (LSPR) induced by the coupling of the incident electric field with the free electrons in the metal [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, most important issue is to improve the efficiency of photoelectric conversion. One of the methods for upgrading these devices is the use of localized surface plasmon resonance (LSPR) induced by the coupling of the incident electric field with the free electrons in the metal [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Recently, we found the large enhancement of photocurrents of a porphyrin or a phthalocyanine derivative or a poly(3-hexylthiophene) as an organic dye in dye-metal NPs composite films on indium-tin-oxide (ITO) electrodes were performed by the electrostatic layer-by-layer adsorption technique [4][5][6][7][8][9][11][12][13] . We also found the remarkable enhancements of photocurrent responses in the composite films of donor -acceptor linked compound and metal NP [silver nanoparticle (AgNP) or gold nanoparticle (AuNP)] on ITO electrodes attributable to the combination of localized surface plasmon resonance (LSPR) due to AgNP or AuNP and photoinduced intramolecular electron-transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that Au and Ag NPs were used as light harvesting efficiency (LHE) factor [1,[6][7][8]. Till now only a few methods of using Ag NPs have been tested in dye synthesized solar cells which include using Ag@SiO 2 [1], atomic layer deposition of Ag NPs [8] and drop casting of Ag [9].…”
Section: Introductionmentioning
confidence: 99%